2014
DOI: 10.1177/0018726714521645
|View full text |Cite
|
Sign up to set email alerts
|

Transformation through tension: The moderating impact of negative affect on transformational leadership in teams

Abstract: Transformational leadership has consistently been argued to enhance diverse team outcomes, yet related research has generated ambiguous findings. We suggest that effectiveness is enhanced in interprofessional teams when transformational leaders engender dynamics that are characterized by interprofessional motivation and openness Corresponding author:Rebecca Mitchell, Newcastle Business School, University of Newcastle, Newcastle, New South Wales 2308, Australia. Email: rebecca.mitchell@newcastle.edu.au 521645H … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 103 publications
(177 reference statements)
1
32
0
Order By: Relevance
“…This research suggests that there are significant professionally based factors promoting and restraining interprofessional collaboration (Currie & Suhomlinova, ) and has led to a gradual increase in research focused on interprofessional teamwork over the past three decades (Richter, Dawson & West, 2011; Thylefors, ). An area of emerging value in this work is leadership and the influence of leaders in interprofessional team performance (Mitchell, Boyle, Parker, Giles, Joyce, & Chiang, ).…”
mentioning
confidence: 99%
“…This research suggests that there are significant professionally based factors promoting and restraining interprofessional collaboration (Currie & Suhomlinova, ) and has led to a gradual increase in research focused on interprofessional teamwork over the past three decades (Richter, Dawson & West, 2011; Thylefors, ). An area of emerging value in this work is leadership and the influence of leaders in interprofessional team performance (Mitchell, Boyle, Parker, Giles, Joyce, & Chiang, ).…”
mentioning
confidence: 99%
“…Particularly, transformational leadership increases group learning goal orientation, which increases group positive affect, while decreasing group avoidance goal orientation, which increases group negative affect. Partially supporting these results, Mitchell et al () found that group negative affective tone can block the impact of openness to diversity on group effectiveness, while it may strengthen the drive to collaborate across professional boundaries. Overall, this newer work has added to previous work on convergent group affect by helping to build a more nuanced nomological network of distinct group affective tones.…”
Section: Outcomes Of Affective Convergence and Divergence In Groupsmentioning
confidence: 91%
“…While negative mood signals a problematic situation and leads to a more cautious and considered interpretation of information (Mitchell et al, 2014), positive moods typically signify that all is going well and the situation is not challenging or problematic (Forgas & Koch, 2013), which encourages more flexible thinking (Baas, De Dreu, & Nijstad, 2008;Bless & Fiedler, 2006;Kaufmann, 2003;Schwarz & Clore, 2003). In addition to this broadened focus on external attention and more expansive, global exploration of information (Fredrickson & Branigan, 2005;Gasper & Clore, 2002), positive mood is also associated with lower internal error monitoring as individuals are less concerned or troubled by their own errors (Pourtois, Vanlessen, Bakic, & Paul, 2017;Vanlessen, De Raedt, Koster, & Pourtois, 2016).…”
Section: Team Positive Mood and Innovationmentioning
confidence: 99%
“…For example, inspirational leadership styles have been found to elicit enthusiasm and optimism (Ashkanasy & Tse, 2000;Tims, Bakker, & Xanthopoulou, 2011), and positive mood has been found to increase task performance in teams led by such leaders (Tsai, Chen, & Cheng, 2009). Therefore, deservedly, mood and emotion have received attention in the leadership literature (e.g., Mitchell et al, 2014;Sy, Côté, & Saavedra, 2005). Despite this strong research focus, the impact of leader, rather than follower, mood has tended to dominate extant research, leading to calls for greater attention to the impact of follower mood on the path between leadership and team outcomes (Glasø, Skogstad, Notelaers, & Einarsen, 2017;van Knippenberg & van Kleef, 2016).…”
mentioning
confidence: 99%